Persistent Invasive Mole: A Case Report - Kusuma, Prathyusha; Neela, Bhargavi; Ramavath, Balasankar (Journal of Pharmacy Practice and Community Medicine)
Gestational trophoblastic disease is a group of interrelated lesions arising from the trophoblastic epithelium of placenta after abnormal fertilization. It is a disease of women with pregnancy related tumors. Invasive mole, a common manifestation of gestational trophoblastic disease is characterized by villi accompanying trophoblastic overgrowths and invasion which penetrate deep into the myometrium sometimes involving peritoneum or vaginal vault. Here we present a case of persistent invasive mole in a patient who underwent dilation and curettage twice with persistent vaginal bleeding and elevated serum β-human Chorionic Gonadotropin levels. Investigations revealed enlarged uterus with adnexal pathology, Histopathological examination of Dilation and Curettage showed presence of villi and trophoblastic tissue, increased serum β-hCG levels. The patient is successfully treated and managed with methotrexate chemotherapy. This study is focused on the significance of follow-up of the patient as there are more chances of recurrence associated with gestational trophoblastic disease.
Keywords: Gestational trophoblastic disease; Invasive mole; β-hCG levels; Chemotherapy; Methotrexate.